PERAN KEPEMIMPINAN DALAM MENDORONG INOVASI DAN KINERJA TIM DI PUSKESMAS: STUDI KASUS PADA PUSKESMAS KEDUNGTUBAN BLORA - HARTONO, HARTONO (FEBI IAI Al Muhammad Cepu, 2024)
The role of transformational leaders in creating innovation is very important for organizations. Transformational leaders are able to provide clear direction and goals for their team, as well as provide the support and guidance needed so that the team can continue to learn and develop. In this way, transformational leaders are able to encourage their teams to continue looking for solutions and new ideas that can improve organizational performance. The characteristics of transformational leaders who are able to create innovation include the ability to provide clear direction and clear goals for their team, as well as being able to provide the necessary support so that the team can continue to learn and develop. Transformational leaders are also able to create a healthy and positive work climate, as well as facilitating effective communication within the team.The transformational leader's strategy in encouraging the team to create innovation includes providing the necessary support so that the team can explore new ideas and develop innovations that can improve organizational performance. Transformational leaders are also able to create a climate that respects risk and failure, as well as creating an open and inclusive climate. The role of transformational leaders in creating a work climate that is conducive to innovation includes creating a positive and respectful work atmosphere